Early Detection of Hypertension (EDH) Skoring dalam Memprediksi Kejadian Hipertensi pada Usia Produktif - Nurpratiwi Nurpratiwi; Debby Hatmalyakin; Mimi Amaludin; Uti Rusdian Hidayat; Ali Akbar; Defa Arisandi; Fauzan Alfikrie (Wiraraja Medika : Jurnal Kesehatan, 2023)
Hypertension is a disease that cannot be cured but can be managed well to maintain optimal patient conditions. The number of people with hypertension is increasing. In addition, hypertension is called a "silent killer" because it can often appear without complaints, so patients do not know they have hypertension. This condition certainly requires a method for prevention in the form of identifying the risk of hypertension through a scoring system approach. Scoring systems have been widely applied in medicine, especially in medical cases, with the aim of predicting patient mortality or prognosis during a disease. This study aims to look at the scoring system for predicting the incidence of hypertension at productive age in Pontianak City. This study used a quantitative method using an analytic observational design with a prospective cohort approach. The number of research respondents was 100 with quota sampling. Bivariate analysis used the ROC test to obtain the AUC value and determine the cut-off point. The results showed an AUC value of 0.984 with a cut-off point value of 7, a sensitivity value of 0.966 and a specificity of 0.869. The EDH Score can be used to detect early cases of hypertension in productive age. The need for development in the form of an information system to facilitate the calculation of scores on the EDH Score instrument.